Tinjauan - Taufik Budi Cahyana; Achmad Wardana; Hudoro Tahdi; Y.H. Yogaswara (LPPM Politeknik Aceh Selatan, 2023)
Indonesia's decision in the procurement of the 4.5th generation Rafale fighter jets was agreed to replace the obsolete aircraft Hawk 109/209 and grounded F-5. The selection of Rafale was not only based on the defense relationship between Indonesia and France that had existed for a very long time but also based on the foreign policy adopted by Indonesia. The free and active foreign policy is shown by several defense equipment owned by Indonesia, not only from a particular country. The government's considerations in choosing the Rafale to strengthen the TNI and cooperation in the defense sector with France include: Advantages of the Rafale Fighter Jet, Long-Term Investment in Indonesian Alutsista, Development of Defense Industry Cooperation, Budget Efficiency, Aspects of Defense and Political Strategy, and Free Guarantee from CAATSA Sanctions. In this case, it is expected that Indonesia will not rely on the procurement of defense equipment from abroad, and the implementation of the Transfer of Technology, Local Content and Offsets on Rafale fighter jets can run as expected, therefore a strategy is needed in accelerating defense acquisition, where there are three strategies for technological development and the defense industry to improve significantly.